Grasshopper diversity in several agricultural areas and savannas in Dompu, Sumbawa Island, Indonesia - Amin Setyo Leksono; Bagyo Yanuwiadi; Ainul Khotimah; Anisa Zairina (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Leksono AS, Yanuwiadi B, Khotimah A, Zairina A. 2021. Grasshopper diversity in several agricultural areas and savannas in Dompu, Sumbawa Island, Indonesia. Biodiversitas 23: 75-80. In Sumbawa Island, the conversion of forests and savannahs into agricultural land has increased rapidly since 2010. This research aims to compare grasshopper species' abundance, richness, and diversity between several farmland and savannas in Dompu, Sumbawa Island. It was conducted at ten locations in Dompu, Sumbawa Island, and included an ecotone, two post-harvested rice farms, two post-harvested corn farms, a mixed farm, a vegetable farm, and three savannas. Furthermore, samples were taken four times from four plots at each location in the post-harvest period from August to September 2021. Grasshopper sampling was carried out using the sweeping method with an insect net with each plot size of 2 x 10 m2. A total of 2264 individual grasshoppers belonging to 30 species and four families were collected from all research sites. The dominant species were Alloteratura sp., Trilophidia annulata, Atractomorpha crenulata, Phlaeoba fumosa, Oxya japonica and, Phlaeoba infumata. The greatest grasshopper species richness and diversity were found in post-harvest rice farms, while the lowest was in the vegetable farm, and most of these species are considered pests. This research shows that the composition of grasshoppers on agricultural land is very similar to that of the adjacent savannah. Hence, monitoring and controlling their presence is necessary by paying attention to savannas as refuge land.